FLOWERING PHENOLOGY AND FLORAL BEHAVIOR OF SCUTELLARIA DISCOLOR COLEBR. AND S. SLAMETENSIS SUDARMONO & B.J. CONN (LAMIACEAE) [FENOLOGI DAN PERILAKU PEMBUNGAAN PADA SCUTELLARIA DISCOLOR COLEBR. DAN 5. SLAMETENSIS SUDARMONO & B.J. CONN (LAMIACEAE)] - Sudarmono, Sudarmono (Research Center for Biology-Indonesian Institute of Sciences, 2010)
The flowering phenology and floral behavior of Scutellaria discolor and S. slametensis were investigated. S. discolor is distributed over a wider range of habitats but S. slametensis is distributed over a restricted area on Mt. Slamet. Observations of flowering phenology and floral behavior were almost the same and pollination of cleistogamous flowers did not occur in both species.Based on our observations on floral and pollinator behavior, we consider both S. discolor and S.slametensis to have chasmo- and cleistogamous flowers.